Structured ZSM-5/SiC foam catalysts for bio-oils upgrading - Ou, Xiaoxia; Wu, Chunfei; Shi, Kaiqi; Hardacre, Christopher; Zhang, Jinsong; Jiao, Yilai; Fan, Xiaolei (2020)
ZSM-5 zeolite coating supported on SiC foams was prepared by a precursor dispersion-secondary growth method and the resulting structured ZSM-5/SiC foam catalyst was used for the proof-of-concept study of catalytic bio-oils upgrading (i.e. deoxygenation of the model compounds of methanol and anisole) in reference to ZSM-5 catalyst pellets. A layer of ZSM-5 coating with inter-crystal porosity on SiC foams was produced by curing the zeolite precursor thermally at 80 °C. The use of SiC foam as the zeolite support significantly improved transport phenomena compared to the packed-bed using ZSM-5 pellets, explaining the comparatively good catalytic performance achieved by the structured ZSM-5/SiC foam catalyst. In comparison with the ZSM-5 pellets, the ZSM-5/SiC foam catalyst showed 100.0% methanol conversion (at the weight hourly space velocity, WHSV, of 8 h–1) and 100.0% anisole conversion (at WHSV =5 h−1) at the initial stage of the processes, while only about 3% were obtained for the ZSM-5 pellets, under the same conditions. Based on the comparative analysis of the characterisation data on the fresh and spent catalysts, the deactivation mechanisms of the ZSM-5/SiC and the ZSM-5 pellet catalysts were explained. The process intensification using SiC foam to support ZSM-5 improved the global gas-to-solid mass transfer notably, and hence mitigating the pore blocking due to the carbon deposition on the external surface of supported ZSM-5.